Validação do guia de acolhimento com classificação de risco em pediatria na prática clínica - Veras, Joelna Eline Gomes Lacerda de Freitas (2016)
With overcrowding and prolonged waiting time in emergencies, the Risk Rating Reception (RRR) of patients, has become an important strategy to improve the quality of care. The Guide RRR in Pediatrics is a clinical evaluation technology, easy to handle and simple presentation, used by nurses in the evaluation of clinical indicators and biophysiological parameters from the main complaint, to adequately identify the priority of patient care, according to the five classification levels: red (Priority I), orange (priority II) yellow (priority III), green (priority IV) and blue (priority V). The objective of the study was to validate the Guide to RRR in Pediatrics in clinical practice. Methodological study, developed in three stages. In the first stage, the content of the first version of the guide was reviewed, through the analysis of two experts on the theme. In the second stage, the interobserver reliability of the 2nd version of the guide between the researcher and two nurses (E1 and E2) trained by the researcher with 206 children and / or adolescents in June 2016 at a pediatric municipal hospital in Fortaleza- CE. In the third stage, the second version of the guide was applied in clinical practice with 400 participants, exclusively by the researcher, in July and August of 2016, in that institution. Data were analyzed in SPSS 20.0, using the Kappa index with a 95% confidence interval (CI) for reliability analysis. The effect of the use of the guide in clinical practice was evaluated through the association between the risk classification and the variables age, sex, weight, risk discriminator, procedures performed and destination after discharge by Fisher-Freeman-Halton exact tests considering statistically significant when p <0.05 and the likelihood ratio with 95% CI. The variables that presented values of p <0.20 entered into the multivariate logistic regression model. The results showed a revised guide in its content, structure and layout, valid and reliable. There was high agreement (Kappa = 0.701) between the researcher and E1 and almost perfect (Kappa = 0.847) with E2, being p <0.001. There was a statistically significant association between risk classification and risk discriminators (p = 0.0001), emergency procedures (p <0.0001) and patient's destination (p = 0.0132). The prevalence of the risk discriminator was found to be respiratory change (207; 51.8%) at priority level IV (green color) (117; 56.5%). The odds ratio (RC) of risk discriminators to be more urgent (orange, yellow and green) compared to non-urgent (blue) ranged from 1 to 12.3 times and 95% CI [1-82,7]. Of the 15 items of greatest urgency analyzed in the guide, more than half (8; 53.3%) had a statistically significant association and 10 (66.7%) had CR> 1, that is, they were more likely to be classified at the level of priority. It was concluded that the Guide to RRR in Pediatrics is a reliable valid health technology, capable of classifying the child's risk in emergency situations to establish the order of priority of care, in order to minimize errors of decision-making by nurses, making possible humanized and quality assistance.